PELAKSANAAN MANAJEMEN SARANA DAN PRASARANA DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MTS. AL-I’ANAH KOSAMBI KABUPATEN KARAWANG - SUHERNI SUHERNI (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2020)
This study aims to determine: 1) Management of planning learning facilities and infrastructure in MTs. Al-I’anah Kosambi, Karawang Regency. 2) Management of the implementation of facilities and infrastructure in MTs. Al-I’anah Kosambi, Karawang Regency. 3) The evaluation of learning facilities and infrastructure in MTs. Al-I’anah Kosambi, Karawang Regency. This research was conducted using a qualitative approach that focused on collecting data obtained from interviews, observations, and documentation. The data source used was selected purposively, and it was snowball sampling. While technical data analysis is done by data reduction, data presentation and conclusion drawing descriptively. From the research conducted, it was concluded that: first, management planning in MTs. Kosambi Al-I'anah Karawang regency is preceded by identifying the needs needed in the learning process starting from the types of facilities and infrastructure, size, quantity, quality and others. Selecting facilities and infrastructure needs according to priority scale. Inventory learning facilities and infrastructure. Estimating the price or budget needed. Determine the time and place of its procurement and appoint the person responsible for carrying out the procurement of facilities and infrastructure. Second, the implementation of facilities and learning infrastructure in improving the effectiveness of learning in MTs. Al-I'anah Kosambi Karawang Regency by regulating the use and utilization of learning facilities and infrastructure with the schedule for using facilities and infrastructure between the teacher and the class who need them in accordance with the lesson schedule. Third, Evaluation of facilities and infrastructure in improving the effectiveness of Islamic Religious Education learning in MTs. Al-I'anah Kosambi Karawang Regency is conducted routinely every semester where educators and educators work together in optimizing the utilization of learning facilities and infrastructure.